The failure of the "new economics" : an analysis of the Keynesian fallacies - Hazlitt, Henry, 1894-1993 (Pickle partners Publishing, 2016)
First published in 1959, this is a line-by-line commentary and refutation of one of the most destructive, fallacious, and convoluted books of the century: John Maynard Keynes's General Theory, published in 1936. In economic science, Keynes changed everything. He supposedly demonstrated that prices don't work, that private investment is unstable, that sound money is intolerable, and that government was needed to shore up the system and save it. It was simply astonishing how economists the world over put up with this, but it happened. He converted a whole generation in the late period of the Great Depression. By the 1950s, almost everyone was Keynesian. However, Hazlitt, the nation's economics teacher, would have none of it. And he did the hard work of actually going through the book to evaluate its logic according to Austrian-style logical reasoning.